Fatal Clostridium septicum febrile neutropenia during adjuvant chemotherapy for early breast cancer. Issue 5 (20th May 2020) - Moreira-Pinto, João; Passos-Coelho, José Luís; Lopes, Fabio; Ataíde, Monica; Oliveira, Paulo
Abstract : We report the case of a 76-year-old female patient with early breast cancer (hormone receptor-positive erbb2 amplified) that had started adjuvant chemotherapy with docetaxel, carboplatin and trastuzumab (TCH). Eight days after the first cycle of TCH chemotherapy, the patient was diagnosed with grade 1 oral mucositis, treated conservatively. The next day she started with nausea, vomiting, chills and fever, followed by a generalised tonicoclonic seizure. She presented to the emergency department with fever, hypotension and mild abdominal tenderness. Grade 4 neutropenia (370 μL/mL) and severe metabolic acidosis were documented. An abdominal CT scan documented extensive ischaemic bowel changes, with gas in portal and mesenteric veins, and pneumoretroperitoneum. Despite broad spectrum antibiotics and fluid resuscitation, she died 4 hours after admitted to hospital. Blood cultures collected on hospital admission eventually grew Clostridium septicum bacteria, an extremely rare infection in patient with breast cancer.